Evolution and Trends in Flexibility Management Research: A Bibliometric Analysis (1971-2025) - Sulistyowati, Tussi; Anwar, Khairil; Pardosi, Pardomuan (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study employs a quantitative method with a bibliometric analysis of flexibility management literature from 1971 to 2025, examining key trends, influential authors, major subject areas, and evolving research focuses. The analysis reveals that publication activity remained low until the early 2000s, followed by a significant increase around 2005, peaking between 2018 and 2022. This surge reflects the growing importance of flexibility management in addressing technological, organizational, and environmental challenges. The most prolific authors, including Ford, J.D., and Johnson, F.A., have made substantial contributions to the field, while the most cited articles primarily focus on resilience, adaptive capacity, and risk management. A subject area analysis highlights the interdisciplinary nature of flexibility management, with Environmental Science (35.2%) and Social Sciences (18.4%) as the dominant fields. An overlay visualization of research evolution indicates a shift from foundational resilience concepts to AI-driven adaptability, digital transformation, and real-time decision-making. Future research should explore AI-driven flexibility models, resilience in digital transformation, adaptive energy systems, and interdisciplinary approaches integrating behavioural economics and cognitive decision-making. This study provides insights into the historical development of flexibility management research and identifies emerging areas warranting further investigation, offering valuable guidance for future studies and practical applications.